Cell osteogenic bioactivity mediated precisely by varying scaled micro-pits on ordered micro/nano hierarchical structures of titanium. (1st July 2022) - Zhang, Yanmei; Wang, Xiankuan; Li, Yaxian; Liang, Jianhe; Jiang, Pinliang; Huang, Qiaoling; Yang, Yun; Duan, Hongping; Dong, Xiang; Rui, Gang; Lin, Changjian
Abstract: Hierarchical surface structures with micro–nano scale play a crucial role in regulation of cell proliferation and osteogenic differentiation. It has been proven that cells are extremely sensitive to the nanoscaled structure and show multifarious phenotypes. Though a vital function of microstructure on osseointegration has been confirmed, the cell performances response to different microscaled structure is needed to be further dissected and in depth understood. In this work, the ordered micro–nano hierarchical structures with varying micro-scaled pits were precisely fabricated on titanium successfully by the combination of electrochemical, chemical etching and anodization as well. In vitro systematical assessments indicated that the micro–nano multilevel structures on titanium exhibited excellent cells adhesion and spreading ability, as well as steerable proliferation and osteogenic differentiation behaviors. It is shown that smaller micro-pits and lower roughness of the hierarchical structures enabled faster cell propagation. Despite cell growth was delayed on micro–nano titanium with relatively larger cell-match-size micro-pits and roughness, osteogenic-specific genes were significantly elevated. Furthermore, the alkaline phosphatase activity, collagen secretion and extracellular matrix mineralization of MC3T3-E1 on multi-scaled titanium were suppressed by a large margin after adding IWP-2 (an inhibitor of Wnt/β-catenin signal pathway), indicating this pathway played a crucial part in cell osteogenic differentiation modulated by micro–nano structures. Graphical Abstract: